2021
DOI: 10.1172/jci.insight.145715
|View full text |Cite
|
Sign up to set email alerts
|

αVβ8 integrin targeting to prevent posterior capsular opacification

Abstract: Fibrotic posterior capsular opacification (PCO), a major complication of cataract surgery, is driven by transforming growth factor β (TGFβ). Previously, αV integrins were found to be critical for the onset of TGFβ-mediated PCO in vivo, however, the functional heterodimer was unknown. Here, β8 integrin conditional knockout (β8ITGcKO) lens cells (LCs) were observed to attenuate their fibrotic responses, while both β5 and β6 integrin null LCs underwent fibrotic changes similar to WT at 5 days PCS. RNAseq revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…However, it appears that the inflammatory response is not globally attenuated as S100a9 expression upregulated normally in Egr1KO LECs at 24 h PCS ( Figure 6 A,C). Further protein levels for the fibrotic markers Gremlin1 and Tenascin C upregulate in wildtype LECs by 48 h PCS as previously reported [ 11 , 62 ] and this upregulation was not affected in Egr1KO LECs ( Figure 6 B,C) even though Egr1 has been reported to regulate the fibrotic response in other systems [ 63 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…However, it appears that the inflammatory response is not globally attenuated as S100a9 expression upregulated normally in Egr1KO LECs at 24 h PCS ( Figure 6 A,C). Further protein levels for the fibrotic markers Gremlin1 and Tenascin C upregulate in wildtype LECs by 48 h PCS as previously reported [ 11 , 62 ] and this upregulation was not affected in Egr1KO LECs ( Figure 6 B,C) even though Egr1 has been reported to regulate the fibrotic response in other systems [ 63 ].…”
Section: Resultssupporting
confidence: 84%
“…While modern cataract surgery has revolutionized the practice of ophthalmology, like all surgeries, it results in elevated inflammation at the wound site [ 4 , 5 , 6 ] leading to post-surgical pain and discomfort. As ocular inflammation can also trigger retinal edema, retinal detachment, and exacerbate uveitis [ 6 , 7 , 8 , 9 , 10 ] as well as fibrotic conditions [ 11 , 12 ], it is typically aggressively treated with a combination of steroids and NSAIDs either via eye drops [ 13 , 14 ] or “drop-less” methods [ 15 ] which instill anti-inflammatories into the eye at the time of surgery. While these drugs are highly effective, post-surgical inflammation still does occur, and is clinically observed as “flare” [ 16 ] defined by increases in the protein concentration of the aqueous humor and the influx of inflammatory cells into the anterior segment of the eye by 20–24 h post cataract surgery (PCS) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…αVβ6 is thought to activate TGFβ through its association with an RGD peptide in the latency-associated peptide ( Sheppard, 2004 ) and in human capsular bags αVβ6 integrin expression was shown to be increased compared to cultured, intact whole lenses that have not been injured ( Figure 1 ) ( Sponer et al, 2005 ). However, recent work has revealed that the β8 heterodimer of αV plays a major role in regulating injury induced fibrosis in the lens ( Shihan et al, 2021 ). Following cataract surgery, β8 integrin–conditional knockout (β8ITG-cKO) mice exhibited an attenuated fibrotic response in the lens as compared to WT mice.…”
Section: Cell Adhesion Changes and Activation Of Tgfβ In Lens Fibrosismentioning
confidence: 99%
“…[17][18][19] Among them, preventing PCO based on the combination of IOL materials and antiproliferative drugs has attracted more attention. [20][21][22][23][24] Such surface design of IOL can inhibit the proliferation and migration of residual LECs after the surgery and help to achieve the joint enhancement of PCO prevention by maintaining the release of antiproliferative drugs in the eye. [25][26][27] The traditional impregnation loading method inevitably has the disadvantage of burst release.…”
Section: Introductionmentioning
confidence: 99%